2015
DOI: 10.1097/md.0000000000001778
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Acute Promyelocytic Leukemia With a Rare Karyotype of ider(17)(q10)t(15;17) and Favorable Outcome

Abstract: Acute promyelocytic leukemia (APL) is a specific malignant hematological disorder with a diagnostic hallmark of chromosome translocation t(15;17)(q22;q21). As a very rare secondary cytogenetic aberration in pediatric APL, ider(17q) (q10)t(15;17) was suggested to be a poor prognostic factor based on previous case reports.Here, we report a pediatric APL case with a rare karyotype of ider(17)(q10)t(15;17). Bone marrow aspiration, immunophenotyping, molecular biology, cytogenetic, and fluorescence in situ hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Variant translocation described as simple translocation involving chromosome 15 or 17 with any other chromosomes or complex translocations characterized by the involvement of additional chromosomes in addition to chromosomes 15 and 17 (4)(5)(6)(20)(21)(22)(23)(24) was found in two patients in the analyzed group. In one of them, t(11;17) (q23;q12) was identified, and in the second complex, translocation involving chromosomes 4, 15, 16, and 17 was found.…”
Section: Discussionmentioning
confidence: 99%
“…Variant translocation described as simple translocation involving chromosome 15 or 17 with any other chromosomes or complex translocations characterized by the involvement of additional chromosomes in addition to chromosomes 15 and 17 (4)(5)(6)(20)(21)(22)(23)(24) was found in two patients in the analyzed group. In one of them, t(11;17) (q23;q12) was identified, and in the second complex, translocation involving chromosomes 4, 15, 16, and 17 was found.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggested that ider(17)(q10)t(15;17) (q22;q12) might be a poor prognostic factor in APL [1,3,[12][13][14][15]. Therefore, some reports showed that the clinical course of patients with ider(17)(q10)t(15;17) (q22;q12) did not seem to differ from that of the typical t(15;17)(q22;q12) [13,15]. The role of ider(17)(q10)t(15;17)(q22;q12) in APL is still an ongoing investigation and is limited by the small number of published cases.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever an ider(17q) is generated as a secondary mutation, not only the genetic information contained in the long arm is duplicated, but also genes from the short arm are lost, as is the case for the tumor suppressor gene TP53, among others. Significance of the ider(17q) in APL severity at diagnosis, response to treatment, or overall survival is still uncertain and limited by its low incidence [Schoch et al, 1996;Chou et al, 1997;Kaleem et al, 1999;Xu et al, 2001;Manola et al, 2010;Kim et al, 2011;Hu et al, 2014;He et al, 2015;Liu et al, 2020]. We here present two cases with APL who acquired an ider(17q) as a secondary chromosomal change.…”
Section: Introductionmentioning
confidence: 96%